Fuzzy current analysis-based fault diagnostic of induction motor using hardware co-simulation with field programmable gate array - Aib, A.; Khodja, Djalal Eddine; Chakroune, Salim; Rahali, H. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Presently, signal analysis of stator current of induction motor has become a popular technique to assess the health state of asynchronous motor in order to avoid failures. The classical implementations of failure detection algorithms for rotating machines, based on microprogrammed sequential systems such as microprocessors and digital signal processing have shown their limitations in terms of speed and real time constraints, which requires the use of new technologies providing more efficient diagnostics such as application specific integrated circuit or field programmable gate array (FPGA). The purpose of this work is to study the contribution of the implementation of fuzzy logic on FPGA programmable logic circuits in the diagnosis of asynchronous machine failures for a phase unbalance and a missing phase faults cases. The purpose of this work is to study the contribution of the implementation of fuzzy logic on FPGA programmable logic circuits in the diagnosis of asynchronous machine failures for a phase unbalance and a missing phase faults cases. Methodology. In this work, we propose hardware architecture on FPGA of a failure detection algorithm for asynchronous machine based on fuzzy logic and motor current signal analysis by taking the RMS signal of stator current as a fault indicator signal. Results.The validation of the proposed architecture was carried out by a co-simulation hardware process between the ML402 boards equipped with a Virtex-4 FPGA circuit of the Xilinx type and Xilinx system generator under MATLAB/Simulink. Originality. The present work combined the performance of fuzzy logic techniques, the simplicity of stator current signal analysis algorithms and the execution power of ML402 FPGA board, for the fault diagnosis of induction machine achieving the best ratios speed/performance and simplicity/performance. Practical value.The emergence of this method has improved the performance of fault detection for asynchronous machine, especially in terms of hardware resource consumption, real-time online detection and speed of detection.

В даний час аналіз сигналу струму статора асинхронного двигуна став популярним методом оцінки стану працездатності асинхронного двигуна, щоб уникнути відмов. Класичні реалізації алгоритмів виявлення несправностей машин, що обертаються, засновані на мікропрограмних послідовних системах, таких як мікропроцесори і цифрова обробка сигналів, показали свої обмеження з точки зору швидкості та обмежень у реальному часі, що вимагає використання нових технологій, що забезпечують більш ефективну діагностику. наприклад, інтегральна схема для конкретної програми або програмована вентильнаматриця (FPGA). Метою даної є дослідження внеску реалізації нечіткої логіки на програмованих логічних схемах FPGA в діагностику відмов асинхронних машин при несиметрії фаз і обривах фази. Методологія. У цій роботі ми пропонуємо апаратну архітектуру на FPGA алгоритму виявлення відмов асинхронної машини на основі нечіткої логіки та аналізу сигналів струму двигуна, приймаючи середньоквадратичний сигнал статора струму як сигнал індикатора несправності. Результати. Валідація запропонованої архітектури проводилася шляхом апаратного моделювання між платами ML402, оснащеними схемою Virtex-4 FPGA типу Xilinx та генератором системи Xilinx під керуванням MATLAB/Simulink. Оригінальність. Дана робота поєднала в собі ефективність методів нечіткої логіки, простоту алгоритмів аналізу сигналів струму статора та виконавчу потужність плати ML402 FPGA для діагностики несправностей асинхронних машин, досягаючи найкращих співвідношень швидкість/продуктивність та простота/продуктивність. Практична цінність. Поява цього методу покращила продуктивність виявлення несправностей асинхронної машини, особливо з точки зору споживання апаратних ресурсів, онлайн виявлення в реальному часі та швидкості виявлення.
Keywords: asynchronous machine; fuzzy current analysis; field programmable gate array; hardware co-simulation; асинхронні машини; аналіз нечітких струмів; програмована вентильна матриця; апаратне спільне моделювання